2017
DOI: 10.18178/ijesd.2017.8.2.938
|View full text |Cite
|
Sign up to set email alerts
|

Satellite Application for Felt Earthquake Events in Sabah, Malaysia

Abstract: I. INTRODUCTIONEarthquake occurrence is one of the significant events in nature that causes both irretrievable financial and physical harm. Apparently the monitoring of earthquake is essential in developing Early Warning System (EWS) for disaster management is proposed. The geological and seismotectonic information of the South East Asia region showed that Malaysia do face certain degree of threats from major earthquakes originating from the surrounding regions as well as from local earth tremors [1]. These po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 3 publications
0
4
0
Order By: Relevance
“…Aside from above, previously, on July 26, 1976, a severe earthquake centered in Lahad Datu, Sabah, with a moment magnitude of Mw 5.8 struck east Malaysia [46]. In addition, recently an earthquake that happened in Ranau, Sabah on 5th June 2015 with a moment magnitude of Mw 6.0 has shocked the Southeast Asian public because it was unexpected.…”
Section: Seismicitymentioning
confidence: 91%
See 1 more Smart Citation
“…Aside from above, previously, on July 26, 1976, a severe earthquake centered in Lahad Datu, Sabah, with a moment magnitude of Mw 5.8 struck east Malaysia [46]. In addition, recently an earthquake that happened in Ranau, Sabah on 5th June 2015 with a moment magnitude of Mw 6.0 has shocked the Southeast Asian public because it was unexpected.…”
Section: Seismicitymentioning
confidence: 91%
“…A significant number of specialists were also taken aback by the damage it caused. This occurrence of earthquake is regarded as Malaysia's largest recorded earthquake, and 18 people were killed as a result of it [46,47].…”
Section: Seismicitymentioning
confidence: 99%
“…W j = I j p ij (8) where P ij (1) is the frequency ratio; a and b are the domain (percentage of the total area covered by each class) and past seismic activities' percentages respectively; (P ij ) (4) is the probability density; H j (5) and H jmax (6) represent entropy values with j = 1, . .…”
Section: Implementation Of Index Of Entropy (Ioe)mentioning
confidence: 99%
“…Evidence data from the Minerals and Geoscience Department (JMG) reported that Ranau has strong topographic relief and even moderate magnitude earthquakes would generate large-scale mass movements of land; landslides and mud-floods [8]. These issues created urgent needs for the general population especially for the people living in the affected zone and required immediate solutions towards disaster recovery and preparedness; prompting research-based outputs [4].…”
Section: Introductionmentioning
confidence: 99%